Can Scoliotic Discs Be Controls for Molecular Studies in Intervertebral Disc Research? Insights From Proteomics. Issue 4 (May 2022) - Rajasekaran, S.; Tangavel, Chitraa; Anand, K. S. Sri Vijay; Soundararajan, Dilip Chand Raja; Nayagam, Sharon Miracle; Sunmathi, R.; Raveendran, M.; Shetty, Ajoy Prasad; Kanna, Rishi Mugesh; Pushpa, B. T.
Study Design: Proteomic analysis of human intervertebral discs. Objectives: To compare the characters of scoliotic discs and discs from magnetic resonance imaging (MRI)–normal voluntary organ donors controls used in disc research employing proteomics and establish "true controls" that can be utilized for future intervertebral disc (IVD) research. Methods: Eight MRI-normal discs from 8 brain-dead voluntary organ donors (ND) and 8 scoliotic discs (SD) from 3 patients who underwent anterior surgery for adolescent idiopathic scoliosis were subjected to tandem mass spectrometry, and further analysis was performed. Results: Mass spectrometry identified a total of 235 proteins in ND and 438 proteins in the SD group. Proteins involved in extracellular matrix integrity (Versican, keratins KRT6A, KRT14, KRT5, and KRT 13A1, A-kinase anchor protein 13, coagulation factor XIII A chain, proteoglycan 4) and proteins involved in transcription and DNA repair (Von Willebrand factor A domain-containing 3B, eukaryotic initiation factor 2B, histone H4, leukocyte cell–derived chemotaxin 2) were found to be downregulated in SD. Inflammatory proteins (C3, C1S), and oxidative stress response proteins (peroxiredoxin-2, 6, catalase, myeloperoxidase, apolipoprotein E) were found to be upregulated in SD. These changes were reflected at the pathway level also. Conclusion: Findings of our study confirm that scoliotic discs have an abundance of inflammatory, oxidative stress response proteins, which are either absent or downregulated in the ND group indicating that scoliotic discs are not pathologically inert. Furthermore, this study has established MRI-normal discs from voluntary organ donors as the "true" control for molecular studies in IVD research.